SCIENTIFIC BASES FOR THE USE OF PHYTOGENIC SUPPLEMENTS IN PIG FATTENING - Chyzhanska, N. V.; Kuzmenko, L. М.; Polishchuk, A. A. (Scientific Progress & Innovations, 2021)
The analysis of scientific papers of Ukrainian and foreign researchers on the use of phytogenic supplements for livestock feeding has been conducted. In fact, modern intensification of manufacturing food products of animal origin makes serious demands as to the quality of feed for all kinds of animals and poultry. Various feed supplements together with the main raw product components affect the quality of feeds. This is why the researches are currently being conducted to determine the impact of bioactive substances and feed supplements in premixes and combined feed on the quality of livestock products. Biosecurity of manufacturing organic competitive livestock products with the preservation of the physiological normality of farm animals and humans who consume the products is an ex-tremely urgent problem for Ukraine. For this reason, natural, plant-based supplements have become widely used in recent years. Phytobiotics in animal and poultry feeding have been actively used since banning feed antibiotics in the European Union countries as the excessive use of antibiotics has a negative effect on the animal body. For this rea-son, a new concept of feeding animals with phytobiotics was developed. Phytogenic compounds contribute to all systems of the organism and have no side effects, even with long-term use. The systemic effect of phytobiotics on the organism of farm animals is not only related to their antimicrobial action but also to their positive effect on digestive processes. They make it possible not only to add biologically active substances to the ration, but also they contain a wide range of essential nutrients for the functioning of the farm animal organism. Phytogenic feed supplements are used as an alternative to antibiotics to stimulate growth and increase animal productivity, and herbal immunomodu-latory feed supplements improve immune system functions in young farm animals. The use of plant polyphenols to deal with oxidative stress and inflammatory processes in farm animals has also been considered. Due to the use of phenolic substances and essential oil contained in phytobiotics, the quality of animal products is improved. By add-ing them into the diet compositions, it is possible to ensure increased productivity and normalize animal homeostasis indicators under the conditions of industrial technologies.